Impact of Dual Coding Strategy to Enhance Students’ Retention of Scientific Concepts in Middle Schools - Mir, Kanza Junaid; Fatima, Syeda Aliya; Fatima, Syeda Tasneem (Annals of Human and Social Sciences, 2023)
Recognizing the significance of cultivating enduring conceptual understanding, this study seeks to explore the impact of the dual coding strategy on mitigating the observed challenges in scientific retention. Dual coding, rooted in Allan Paivio's theory posits that combining verbal and visual elements enhances learning and memory recall. This theoretical framework suggests that integrating dual coding into middle school science instruction may bridge the gap between immediate comprehension and long-term retention (Clark & Paivio, 1991; Mayer & Sims, 1994). The literature review within this study delves into existing research on the effectiveness of dual coding in enhancing students' memory retention and conceptual understanding in science education. It examines studies exploring the practical implementation of dual coding, its cognitive benefits, and potential challenges, specifically focusing on middle school settings. By investigating the impact of dual coding on scientific retention, this study aimed to provide actionable insights for middle-year educators seeking to address the observed disparity between classroom activities and assessment outcomes. The findings of (Chen et al., 2017) may not only contribute to the pedagogical discourse on science education, but also offer practical strategies for teachers to optimize their instructional approaches, ultimately fostering a more enduring grasp of scientific concepts among middle school students.